ANALISIS KONSEP BANGUNAN HIJAU PADA ASPEK KESEHATAN DAN KENYAMANAN RUANG KANTOR DIREKSI PT. HUTAMA KARYA DI STABAT - Harni Dwi Pratiwi; Peranita Sagala; Dara Wesdianti (Jurnal Arsitektur ARCADE, 2023)
Abstract: The current infrastructure development process pays little attention to the impact it has on humans and the environment, for this reason it is necessary to apply the green building concept to maintain environmental balance. Office of the Directors of PT. Hutama Karya at Stabat is an office intended for PT. Hutama Karya Infrastructure is a spin off company from the Roads and Bridges Division as a contractor for the Binjai – Langsa Trans Sumatra Toll Road project. The Office of the Board of Directors was chosen as the object of research to determine the extent to which buildings located around rice fields and settlements are implementing sustainable green buildings with the aim of identifying and analyzing the application of green buildings to the health and comfort aspects of space in accordance with GBC Indonesia's greenship. The method used in the research on the analysis of the green building concept on the health and comfort aspects of the PT Hutama Karya board of directors office at Stabat is a qualitative and quantitative method which results in the conclusion that the office of the directors of Gohor criteria for a no-smoking campaign, thermal comfort, noise level, and user comfort. Points on the health and comfort aspects of space at the Office of  Gohor Directors earned 7 points with a percentage of 5.9% of the maximum total points of 20 points with a percentage of 17.09% in accordance with the principles of green building assessment version 1.1Keywords: Green Building, Directors Office, Indoor Health and ComfortAbstrak: Proses pembangunan infrastuktur saat ini kurang memperhatikan dampak yang ditimbulkan terhadap manusia dan lingkungan, untuk itu perlu menerapkan konsep bangunan hijau untuk menjaga keseimbangan lingkungan. Kantor Direksi PT. Hutama Karya di Stabat merupakan kantor yang diperuntukan untuk PT. Hutama Karya Infrastruktur perusahaan spin off dari Divisi Jalan dan Jembatan sebagai kontraktor proyek Jalan Tol Trans Sumatera sesi Binjai – Langsa. Kantor Direksi ini dipilih sebagai objek penelitian untuk mengetahui sejauh mana bangunan yang berada disekitar lahan persawahan dan pemukiman dalam penerapan bangunan hijau yang berkelanjutan dengan tujuan mengidentifikasi dan menganalisa penerapan green building pada aspek kesehatan dan kenyamanan ruang sesuai dengan greenship GBC Indonesia. Metode yang digunakan dalam penelitian analisis konsep bangunan hijau pada  aspek kesehatan dan kenyaman ruang kantor direksi PT Hutama Karya di Stabat adalah metode kualitatif dan kuantitatif yang menghasilkan kesimpulan bahwa Kantor Direksi Gohor mencapai kriteria kampanye dilarang merokok, kenyamanan termal, tingkat kebisingan, dan kenyamanan pengguna. Poin pada aspek kesehatan dan kenyamanan ruang pada Kantor Direksi Gohor memperoleh 7 poin dengan persentasi 5,9 % dari total poin maksimal sebesar 20 point  dengan persentasi 17,09% sesuai prinsip penilaian bangunan hijau terbangun versi 1.1.Kata kunci : Bangunan Hijau, Kantor Direksi, Kesehatan dan Kenyamanan Ruang